Consensus of Minimally Invasive and Multidisciplinary Comprehensive Treatment for Hepatocellular Carcinoma – 2020 Guangzhou Recommendations - Chen, Qi-Feng; Li, Wang; Yu, Simon Chun-ho; Chou, Yi-Hong; Rhim, Hyunchul; Yang, Xiaoming; Shen, Lujun; Dong, Annan; Huang, Tao; Huang, Jinhua; Zhang, Fujun; Fan, Weijun; et al. (Frontiers in Oncology, 2021)
In China, the majority of patients with hepatocellular carcinoma (HCC) result from long-term infection of hepatitis B. Pathologically, HCC is characterized by rich blood supply, multicentric origins, early vascular invasion and intrahepatic metastasis. Therefore, HCC is not a local disease but a systemic disease at the beginning of its occurrence. For this reason, a comprehensive treatment strategy should be adopted in the management of HCC, including local treatments (such as surgical resection, radiofrequency ablation, microwave ablation, chemical ablation and cryoablation, etc.), organ-level treatments (such as transcatheter arterial infusion of chemotherapy and transcatheter arterial chemoembolization [TACE]), and systemic treatments (such as immunotherapy, antiviral therapy and molecular targeted therapy, etc.). This consensus sets forth the minimally-invasive and multidisciplinary comprehensive guideline of HCC, focusing on the following eight aspects: (1) find the intrahepatic lesion and make precise staging; (2) TACE combined with ablation or ablation as the first choice of treatment for early stage or small HCC; (3) infiltrating HCC should be regarded as an independent subtype of HCC; (4) minimally-invasive comprehensive treatment could be adopted in treating metastatic lymph nodes; (5) multi-level subdivision of M-staging should be used for individualized treatment and predicting prognosis; (6) HCC with severe hepatic decompensation is the only candidate criterion for liver transplantation; (7) bio-immunotherapy, traditional Chinese medicine therapy, antiviral therapy, and psychosocial and psychopharmacological interventions should be advocated through the whole course of HCC treatment; (8) implementation of multicenter randomized controlled trials of minimally-invasive therapy versus surgery for early and intermediate stage HCC is recommended.